ANALISIS FAKTOR â FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DI WILAYAH KPP PRATAMA - Wurianti, Exti Lusiani Ega; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
One of the elements of state income which is always chosen as the main revenue is tax. This research is meant to examine the consciousness of paying tax has an influence to the compliance of to pay tax, to examine the comprehension and the knowledge to pay tax has an influence to the compliance to pay tax, to examine good perception on tax system has an influence to the compliance to pay tax, to examine whether the service quality to pay tax has an influence to the compliance to pay tax, to examine whether the socialization has an influence to the compliance to pay tax. This research is an associative research. The population is taxpayers in the area of KPP Pratama Surabaya Wonocolo. The sample collection technique has been done by using purposive sampling and 75 taxpayers have been selected as samples. This research applies primary data the questionnaires are issued to the taxpayers and it contains closed questions. The results of the research are: (1) the consciousness of paying tax has an influence to the compliance to pay tax; (2) the comprehension and the knowledge to pay tax has an influence to the compliance to pay tax; (3) the good perception on tax system has an influence to the compliance to pay tax; (4) the service quality to the taxpayers has an influence to the compliance to pay tax; (5) the socialization has an influence to the compliance to pay tax.Keywords: Consciousness, Comprehension and Knowledge to pay Tax, Service Quality, Socialization